MAKING IT WORK. (American City & County, 2011)
The article focuses on the modernization of the communications and collaboration technology of the state of Montana in 2010. The objective of the scheme is to aid its growing mobile workforce in working more effectively using desktop and handheld devices. The unified communications (UC) technology of Montana was upgraded to Microsoft Exchange Server 2010. One of the new features of the technology is allowing teleworkers to synchronize various mobile devices.